Three analytical schemes to analyze international trafficking in people: in search of a political conception of violence (Research, Society and Development, 2021)
The objective of this essay is to delimit an analytical scheme on International Trafficking in Persons (ITP), considering its peculiarities, in search of a sociological and juridical conception that assesses the notion of the trafficked person and the status of the victim. Methodologically, we undertake an exploratory study, in order to achieve a descriptive objective, based on bibliographic, documentary and statistical procedures. Thus, we delimit the need for the articulation of several social, political and economic elements that can account for a multifaceted, economical, sociological and political phenomenon that affect the ways in which ITP takes root in the structure of a country. We therefore developed a conceptual, sociological-legal and political tripartite scheme. The three schemes can allow a more accurate reading of a crime no longer read under just one lens. We refer to the idea that a political conception of International Trafficking in Persons demands a sociological conception that analyzes social dynamics, with a view to guaranteeing the victim's rights, in order to stop this crime.